Denaturation of the SARS-CoV-2 spike protein under non-thermal microwave radiation - Pooya Afaghi (Nature Portfolio, 2021)
Abstract SARS-CoV-2, the virus that causes COVID-19, is still a widespread threat to society. The spike protein of this virus facilitates viral entry into the host cell. Here, the denaturation of the S1 subunit of this spike protein by 2.45 GHz electromagnetic radiation was studied quantitatively. The study only pertains to the pure electromagnetic effects by eliminating the bulk heating effect of the microwave radiation in an innovative setup that is capable of controlling the temperature of the sample at any desired intensity of the electromagnetic field. This study was performed at the internal human body temperature, 37 °C, for a relatively short amount of time under a high-power electromagnetic field. The results showed that irradiating the protein with a 700 W, 2.45 GHz electromagnetic field for 2 min can denature the protein to around 95%. In comparison, this is comparable to thermal denaturation at 75 °C for 40 min. Electromagnetic denaturation of the proteins of the virus may open doors to potential therapeutic or sanitation applications.